Comic Strip : A Practical Medium of English Speaking for Vocational Learners - Winda Lutfiyanti (STBA JIA Press, 2021)
Speaking English is essential for vocational learners in applying future job, building career network or even dealing with the future customer. Unfortunately, lack of confidence, practice and appropriate media became several problems that caused the constraints in speaking. The later encouraged the researcher to conduct research and development to design a comic strip for vocational learners. In developing comic strip, there were several steps conducted, they are: 1) need analysis, 2) developing model, 3) expert validation, 4) first revision, 5) try out, and 6) second revision. Need analysis involved the learners and the stakeholders to identify the model needed. The result became the reference in developing model. Later, two experts validated the material and presentation aspects to help the researcher in revising the model. Try out was the next step to unsure that the revised model was appropriate and developed well. Further, the researcher used the result as another reference to complete the model. At the end of the research, the researcher found that the comic strip developed was appropriate in learning speaking the vocational school learners as the users of the model.